1978
DOI: 10.1042/bj1690659
|View full text |Cite
|
Sign up to set email alerts
|

Purification and properties of the S1 secondary alkylsulphohydrolase of the detergent-degrading micro-organism, Pseudomonas C12B

Abstract: The SI secondary alkylsulphohydrolase of the detergent-degrading micro-organism, Pseudomonas C12B, was separated from other alkylsulphohydrolases and purified to homogeneity. Under the experimental conditions used the enzyme completely hydrolysed D-octan-2-yl sulphate (D-1-methylheptyl sulphate), but showed no activity towards the corresponding L-isomer. Additional evidence has been obtained to indicate that it is probably optically stereospecific for D-secondary alkyl sulphate esters with the ester sulphate g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
24
0

Year Published

1981
1981
2004
2004

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 19 publications
2
24
0
Order By: Relevance
“…4) suggests that the enzyme is nonglobular and thus indicates that the protein is monomeric. However, this enzyme appears to be much smaller than the previously described alkylsulfatases S1 from Pseudomonas strain C12B and CS2 from C. terrigena, which have molecular masses of approximately 250 kDa (2,21), and it seems to be more closely related to the inducible enzyme S3 from Pseudomonas strain C12B (molecular mass, 40 to 46 kDa) (26).…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…4) suggests that the enzyme is nonglobular and thus indicates that the protein is monomeric. However, this enzyme appears to be much smaller than the previously described alkylsulfatases S1 from Pseudomonas strain C12B and CS2 from C. terrigena, which have molecular masses of approximately 250 kDa (2,21), and it seems to be more closely related to the inducible enzyme S3 from Pseudomonas strain C12B (molecular mass, 40 to 46 kDa) (26).…”
Section: Discussionmentioning
confidence: 71%
“…It was shown that under appropriate culture conditions Pseudomonas sp. strain C12B produced up to five different alkylsulfatases (three secondary and two primary alkylsulfatases, which are specific for the hydrolysis of sec-and prim-alkyl sulfates, respectively) (2,6,11). In contrast, C. terrigena produced only two secondary alkylsulfatases irrespective of the culture conditions employed (1,14).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, sulphate esters were generally the most readily degradable and had the highest fraction of Biolog-positive isolates, while the sulphonates were more recalcitrant and had the lowest fraction of Biolog-positive results. The SDS-degrading isolate, Pseudomonas C12B, gave positive results for all the classes of sulphated surfactants, a versatility which matches the known battery of sulphatase activity in this organism (Bartholomew et al, 1978;Cloves et al, 1980;Shaw etal., 1980;Bateman etal., 1986;Hales etal., 1986). The LABS-degrading consortium appears to be metabolically diverse and is capable of biodegrading all the sulphated and sulphonated surfactants used during this study.…”
Section: Discussionmentioning
confidence: 91%
“…Longchain esters undergo hydrolysis catalysed by alkyl sulphatases in Pseudumonas sp. (Bartholomew et al, 1978;Bateman et al, 1986;Cloves et al, 1980;Dodgson & White, 1983;Dodgson et al, 1982;Matcham et al, 1977a, b ;Shaw et al, 1980;White & Russell, 1993) but these enzymes cease to function when the alkyl chain 0001-8396 0 1993 SGM length falls below C,. A coryneform species has been shown recently to produce an alkyl sulphatase restricted to primary esters in the C3-C7 chain length range (White & Matts, 1992).…”
Section: Introductionmentioning
confidence: 99%